Enhanced Skin Delivery of Therapeutic Peptides Using Spicule-Based Topical Delivery Systems - Chi Zhang; Jiwen Duan; Yongxiang Huang; Ming Chen (Pharmaceutics, 2021)
This study reports two therapeutic peptides, insulin (INS, as a hydrophilic model peptide) and cyclosporine A (CysA, as a hydrophobic one), that can be administrated through a transdermal or dermal route by using spicule-based topical delivery systems in vitro and in vivo. We obtained a series of spicules with different shapes and sizes from five kinds of marine sponges and found a good correlation between the skin permeability enhancement induced by these spicules and their aspect ratio L/D. In the case of INS, Sponge Haliclona sp. spicules (SHS) dramatically increased the transdermal flux of INS (457.0 ± 32.3 ng/cm2/h) compared to its passive penetration (5.0 ± 2.2 ng/cm2/h) in vitro. Further, SHS treatment slowly and gradually reduced blood glucose to 13.1 ± 6.3% of the initial level in 8 h, while subcutaneous injection resulted in a rapid blood glucose reduction to 15.9 ± 1.4% of the initial level in 4 h, followed by a rise back to 75.1 ± 24.0% of the initial level in 8 h. In the case of CysA, SHS in combination with ethosomes (SpEt) significantly (p < 0.05) increased the accumulation of CysA in viable epidermis compared to other groups. Further, SpEt reduced the epidermis thickness by 41.5 ± 9.4% in 7 days, which was significantly more effective than all other groups. Spicule-based topical delivery systems offer promising strategies for delivering therapeutic peptides via a transdermal or dermal route.